Eco Tourism: Studying Sustainable Tourism Strategies from a Triple Bottom Line Perspective in the Mangrove Forest Area of Bali - Ni Putu Tirka Widanti; Ni Nyoman Diah Utari Dewi; Dewa Ayu Agung Intan Pinatih; Jon Mason (Goodwood Publishing, 2025)
Purpose: The purpose of this study was to analyze sustainable tourism strategies in the Bali Mangrove Forest area using the Triple Bottom Line (TBL) approach, focusing on its economic, social, and environmental impacts. Methodology/approach: This study employed a literature review method to examine various academic sources and policy documents related to ecotourism management in the Ngurah Rai Grand Forest Park (Tahura), Bali. The research framework was based on the Triple Bottom Line approach, evaluating the sustainability aspects of ecotourism. Results/findings: The findings revealed that ecotourism in the Bali Mangrove Forest provides economic benefits by increasing local community income through fisheries and tourism activities. Socially, community participation in ecotourism enhances environmental awareness and engagement in conservation efforts. From an environmental perspective, ecotourism supports mangrove preservation through collaborative conservation programs involving local communities, government, and private sectors. Conclusions: Ecotourism in the Bali Mangrove Forest demonstrates the potential of the TBL approach to balance economic, environmental, and social objectives. It strengthens community livelihoods, fosters conservation awareness, and ensures ecological sustainability. The success of this model highlights the importance of integrating community involvement and cross-sectoral collaboration in sustainable tourism strategies. Limitations: The study relies solely on secondary data without field observations or quantitative measurement of impacts, limiting the depth of empirical validation. Contribution: This study applies the Triple Bottom Line framework to Bali’s mangrove ecotourism, providing insights for policymakers and practitioners to develop strategies that balance economic growth, social welfare, and environmental conservation.